2016
DOI: 10.1038/srep27137
|View full text |Cite
|
Sign up to set email alerts
|

An isoform of Nedd4-2 is critically involved in the renal adaptation to high salt intake in mice

Abstract: Epithelial sodium channels (ENaCs) play critical roles in the maintenance of fluid and electrolyte homeostasis, and their genetic abnormalities cause one type of hereditary salt-sensitive hypertension, Liddle syndrome. As we reported previously, both human and rodent Nedd4L/Nedd4-2 showed molecular diversity, with and without a C2 domain in their N-terminal. Nedd4L/Nedd4-2 isoforms with a C2 domain are hypothesized to be related closely to ubiquitination of ENaCs. We generated Nedd4-2 C2 domain knockout mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…The Nedd4-2 C2 domain is encoded by exon 2 in chromosome 18 of mice, and Nedd4-2 C2 KO mice show salt-sensitive hypertension under high oral salt intake, as reported previously [21]. There were no significant differences between the body weights of Nedd4-2 C2 KO mice and their WT (wild type) littermates, as shown in Table 1.…”
Section: Resultssupporting
confidence: 80%
“…The Nedd4-2 C2 domain is encoded by exon 2 in chromosome 18 of mice, and Nedd4-2 C2 KO mice show salt-sensitive hypertension under high oral salt intake, as reported previously [21]. There were no significant differences between the body weights of Nedd4-2 C2 KO mice and their WT (wild type) littermates, as shown in Table 1.…”
Section: Resultssupporting
confidence: 80%
“…In our study, we observed that NEDD4L-dC2 was more potent at ubiquitinating CRTC3 than the form of NEDD4L containing the C2 domain, suggesting that different tissue types may possess double feedback regulation mechanisms to ensure that CRTC3 signaling is turned off. Recently, NEDD4L C2 domain-specific knockout mice have been generated (35). Because NEDD4L-dC2 was more active in ubiquitinating CRTC3, it would be interesting to investigate whether CRTC3 protein levels and lipid metabolism are elevated in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous prior reports have shown that NEDD4-2 interacts with and ubiquitylates ENaC, reducing channel cell surface expression. [24][25][26]28,32,53,54 The physiologic relevance of ENaC/NEDD4-2 interactions has largely been explored within the context of Liddle syndrome or signaling pathways that block NEDD4-2 activity. However, a rationale explaining why NEDD4-2 was selected during evolution to tonically inhibit ENaC activity when aldosterone levels are low has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Although NEDD4-2 is best characterized as an ENaC inhibitor, [24][25][26][27][28][29][30][31][32] it was recently shown that its role is more complex. Both in vitro, as well as in NEDD4-2 knockout (Nedd4L Pax8/LC1 ) mice given a high Na + diet (HSD), NEDD4-2 acts as a NCC inhibitor, 20,21 whereas it affects ENaC to a lesser degree.…”
mentioning
confidence: 99%